Foldable laptop table / Muhammad Azman Azamy - Azamy, Muhammad Azman (Faculty of Applied Sciences, 2019)
Foldable table are the types of the furniture has become an increasingly popular in market. The market trend is changing drastically follow the furniture industries entire world. The best design of product that able to achieve the functional be the point in order to gained the high profit. This study was conducted to exposed the new design of foldable product. Other than that, to make the survey of the foldable laptop table in design, commercialized, and safety of the product. This report is present about the designing and functional of a foldable laptop table. Based on the title of the project, the student has to come up with the new design of foldable laptop table that have the storage purpose. The main objective of the project is to apply the safety for the laptop with a special purpose to secure the laptop and to produce the design of the modem foldable laptop table by using the wood pallet from Pine wood (Pinus radiata).There are several scope of this project consist of ergonomic folding table and design with the safety purpose. The software that used for designing the concept of foldable laptop table is Sketch Up. This software is able to provide drawing in two dimensional and three dimensional views. The concept that applied on the design of the product is modem and foldable.